Evaluation for Major Irrigation Projects - Some Case Studies - Planning Commission (Planning Commission, 1965)
There are many problem-areas associated with major irrigation projects. These range from the initial investment decisions based on given priorities and criteria to the final use of the irrigation facilities and their impact. for a project, already selected, the areas of study may, broadly speaking, be classified as : (i) the engineering aspects of the design and structure of irrigation works; (ii) administrative problems of execution and implementation of irrigation projects; (iii) agricultural problems of utilisation of the irrigation facilities, especially in their bearing on cropping pattern, water requirements of crops, water utilisation, etc.; and (iv) analysis of costs vis-a-vis actual and expected benefits.
Programme Evaluation Organisation Planning Commission Government of India